National and regional differences in meningococcal vaccine recommendations for individuals at an increased risk of meningococcal disease - Cynthia Burman; Jamie Findlow; Helen S. Marshall; Marco A.P. Safadi (Taylor & Francis Group, 2023)
Introduction Invasive meningococcal disease (IMD) is a severe, life-threatening condition caused by infection with Neisseria meningitidis. Currently available vaccines offer protection against the five most common meningococcal disease-causing serogroups and include monovalent and quadrivalent conjugate vaccines (MenA, MenC, MenACWY vaccines) and outer membrane vesicle- and/or recombinant protein-based vaccines (MenB vaccines). Areas covered Country and regional immunization programs target populations susceptible to IMD and typically emphasize the highest-risk age groups (i.e., infants, adolescents/young adults, and the elderly); however, additional groups are also considered at an elevated risk and are the focus of the current review. Specific increased-risk groups include individuals with underlying immunocompromising medical conditions, university/college students, Indigenous people, laboratory workers, military personnel, men who have sex with men, and travelers to areas with hyperendemic IMD. This review compares established meningococcal vaccination recommendations for these vulnerable groups in Europe, the United States, Australia, New Zealand, Israel, Brazil, and Turkey. Expert opinion Recommendations should be standardized to cover all groups at increased risk of IMD.